Prevalence and sociodemographic determinants of uninvestigated dyspepsia in the Czech Republic - Rejchrt, Stanislav; Koupil, Ilona; Kopácová, Marcela; Vorísek, Viktor; Seifert, Bohumil; Pozler, Oldrich; Zivný, Pavel; Douda, Tomás; Palicka, Vladimír; Holcík, Jan; Bures, Jan; European Society for Primary Care Gastroenterology (European journal of gastroenterology & hepatology, 2008)
OBJECTIVE: There are no data on the epidemiology of dyspepsia in Central Europe. The aim of this study was to evaluate the prevalence of uninvestigated dyspepsia in a representative sample of the Czech population. METHODS: A total of 2509 persons, aged 5-100 years, randomly selected from 30 012 individuals in the general population, entered this multicentre, prospective, questionnaire-based epidemiological study. RESULTS: We found a 17% prevalence of long-lasting (>12 months) dyspeptic symptoms in the general population. Two subgroups were distinguished: (i) persons with dyspepsia as the only one long-lasting symptom and themselves feeling otherwise healthy (9%), mostly among younger patients (subgroup A); and (ii) patients with dyspepsia as part of the complex of previously recognized diseases (8%), mostly in older patients (subgroup B). The prevalence of dyspepsia was significantly higher among women. The excess cases of dyspepsia among the highly educated seemed to be cases of dyspepsia of subgroup A, and the higher prevalence of dyspepsia among the lower social classes was largely dyspepsia of subgroup B. Being a widow/widower had a significant effect on the risk of self-reported dyspepsia among 25-64-year-olds. No association between Helicobacter pylori infection and dyspepsia was found. CONCLUSION: The prevalence of uninvestigated dyspepsia in the Czech Republic is comparable with data from other European countries. Clearly distinct subgroups of dyspeptic patients exist that should be further studied.
Keywords: společenská třída; senioři; kouření; Dyspepsia; senioři nad 80 let; krevní tlak; Helicobacter Infections; mladiství; Česká republika; sexuální faktory; Social Class; Middle Aged; mužské pohlaví; Adult; mladý dospělý; stupeň vzdělání; Czech Republic; dítě; dyspepsie; Child; infekce vyvolané Helicobacter pylori; věkové faktory; Aged, 80 and over; Child, Preschool; Smoking; Young Adult; ženské pohlaví; Blood Pressure; Humans; předškolní dítě; Sex Factors; epidemiologické metody; Epidemiologic Methods; lidé středního věku; Age Factors; Helicobacter pylori; dospělí; Educational Status; Female; Aged; Adolescent; lidé; Male